THE EFFECT OF CORPORATE GOVERNANCE ON BANK EFFICIENCY IN INDONESIA - Aisa, Nabila Na'ma (Universitas Ahmad Dahlan, 2018)
The objective of this study is to investigate the effect of board size, audit committee size, and institutional ownership as corporate governance variables on bank efficiency in Indonesia. The populations in this research are all banks listed in Indonesia Stock Exchange (IDX) during the period of 2010-2013. Using purposive sampling, 28 banks are selected as the sample. The data are secondary data from the financial statements and annual reports of the banks. Panel data regression is employed to analyze the data.The findings show that board size has significant negative effect on the efficiency of banks. Other corporate governance variables, audit committee size and institutional ownership, give no significant influence on bank efficiency in Indonesia